Nature defect-mediated room temperature ferromagnetism in lead-free ferroelectric Ba(Zr0.2Ti0.8)O3: A first-principles study - V.T. Lam; N.H. Lam; D.Q. Van; N.T. Trang; J.P. Singh; N.H. Linh; N.H. Thoan; N.N. Trung; D.D. Dung (Next Materials, 2025)
In this study, we employ density functional theory to investigate the impact of vacancy defects on complex lead-free ferroelectric Ba(Zr0.2Ti0.8)O3 material. Our results demonstrate that the undoped Ba(Zr0.2Ti0.8)O3 crystal behaves as a p-type semiconductor with an indirect bandgap of 1.60 eV. The introduction of vacancy defects leads to the formation of both p-type (Ba- and Ti-vacancies) and n-type (O-vacancy) doping characteristics. These defect-induced states result in a notable reduction in the bandgap, from 1.6 eV in pristine BZT to 1.36 eV and 0.37 eV in BZT with Ba and Ti vacancies, respectively, thereby enhancing electrical conductivity and improving the material’s potential for electronic applications. Furthermore, the presence of vacancy defects introduces localized magnetic moments where magnetism of 0.30 μB/f.u., 0.16 μB/f.u., and 0.04 μB/f.u. were obtained for Ti-, Ba- and O-vacancies, respectively, suggesting potential applications in spintronics devices. These magnetic moments primarily originate from the nearby oxygen atoms associated with vacancies, while the contributions from other cations, such as Zr, Ba, or Ti, are less significant. Our analysis of the optical properties further reveals the material’s diverse characteristics, including absorption, dielectric behavior, conductivity, reflectivity, refractive index, and loss function, all of which are crucial for the design of optoelectronic devices.